Tri Angga's Concept Study on the Crea Office Facade in Nusa Dua, Bali - Paramita, Nadia Putri; Tarigan, Riandy; Rianto, Robert (Departement of Architecture, Universitas Islam Indonesia, 2026)
In fact, there have been regulations governing the appearance of buildings in Bali. One of them is the regulation regarding the appearance of Balinese buildings, which must embody the standards of traditional Balinese architecture. The main idea is to use the Tri Angga concept. This means dividing the area, called a mandala. The mandala is divided based on the human body. The human body is seen as having three parts. The research method used is the descriptive method, which involves compiling and analyzing data. This is described in the study through the results of observations. The qualitative method, which involves compiling and analyzing data and sources, is also used. In compiling and analyzing, data related to this study is sorted. Overall, the purpose of this study is to analyze traditional Balinese architecture in buildings as a supporter of regulations in the designed location area and to analyze the aesthetic elements of traditional Balinese architecture in office buildings.